Influência das águas amazônicas no compromisso osmorrespiratório em osteoglossiformes - Ramos, Cleverson Agner (2013)
In the Amazon basin, the Osteoglossiforme order is represented by the species Osteoglossum ferreirai, O. bicirrhosum and Arapaima gigas. Although belonging to the same order, these species show different modes of breathing; while Osteoglossum ssp. is an obligatory water breather, A. gigas shows a gill remodeling during its development, which causes changes in the osmorespiratory compromise with implications for the gill functions which turns more related to the ion exchanges. The rivers of the Amazon basin have different physicochemical features. While the white water rivers (WW) are slightly alkaline and its waters are considered "soft", black water rivers (BW) are practically distilled" having an acidic pH. Such different characteristics between these waters leads to hypothesize that black water rivers can act as an hydrographic barrier, containing the spread of some species. This can be observed in the distribution of some amazonian fish since there are several species unique from black waters while other species are distributed in white and black waters as others only in white waters. In Osteoglossiformes, data from literature suggest O. bicirrhosum as a fish from white water, while A. gigas can be found in black water rivers as white water lakes. This study tested the hydrographic barrier hypothesis exposing the animals in the Amazonian waters and observing responses of ionic fluxes, proliferation of mitochondria rich cells (MRCs), responsible for regulating ion, the presence of mucous cells (MCs) and changes in morphology functional gills.In A. gigas 2000 g there is a fast recovery from ion losses so probably there is no influence of the hydrographic barrier for this specie. Comparing A. gigas and O. bicirrhosum, these fishes are able to ion regulation iin white water environments, mostly by the ion uptake showed in 3 hours. Data from immunohistochemistry for NKA enzyme of MRCs and morphometric data (CRMsFA and density) of these cell indicates that A. gigas 2000g have the gill functions related to ion regulation. About the ion regulation pattern and functional morphology there are similarities between O. bicirrhosum and 200g A. gigas however O. bicirrhosum did not showed the same potential to recovery ion losses as A. gigas.